The girl in the moon - Goodkind, Terry (Skyhorse Publishing, 2018)
"Angela Constantine is a girl born broken. When Angela was young, before she came to realize she had a rare ability, she was a rather ordinary girl. At least, that was what everyone said. But Angela is anything but ordinary. The daughter of a meth addict, she is convinced she was born a freak. Haunted by an abusive childhood, she was forced to become a woman far too soon. And in the process, she became more. Angela Constantine has a secret life. Angela juggles multiple jobs to live a secluded life in a cabin in the mountains. But she also lives a secret life, right under everyone's noses. Because her family's bloodline carries the ability to recognize killers, she adopts a solitary, violent existence in service of her own, personal mission in life. When Angela unexpectedly finds herself the prey of a group of international terrorists, she is the only one who knows the truth of what they are about to do. She might look like an unlikely hero. She might also be our only hope."--